The Effects of Bacterial Enzymes and Biosurfactants on Hydrocarbon Degradation in a Crude Oil Polluted Fresh Water - Olajide, Patience Orobosa (2015)
The present work was designed to identify extracellular enzymes and biosurfactants from five bacterial isolates and investigate their actions on crude oil degradation as a means of bioremediation of hydrocarbon pollution.